Tinjauan Sistem Penataan Arsip Pada Kantor Desa Wayame Kecamatan Teluk Ambon - Merlin Nikijuluw; Vera Paulin Kay; Febiyola Wijaya (P3M Politeknik Negeri Ambon, 2024)
Archive systems were developed with the aim of making it easier to store and retrieve information that is considered important for an organization. The archival process uses a certain system in the preparation and maintenance of archives so that they can be found quickly and precisely and easily destroyed archives based on certain criteria. Archives have an important role in various agencies but this has not received attention in the Wayame village office where the archives in the office are arranged irregularly and only arranged in several folders which are divided into incoming mail folders and outgoing mail folders left piled up on the table. and placed in a filing cabinet. This means that letters that are not archived properly are easily scattered and lost. The aim of this writing is to ensure that all activities for arranging the archives are good and in accordance with archival rules and provide input regarding procedures. good arrangement of archives at the Wayame Village office. The analytical method used in this research is qualitative analysis, namely an analytical technique that describes problems based on theory and expert opinion. The results of this research show that the archives at the Wayame Village office are not in accordance with existing procedures, because the archives in the office are arranged irregularly, and only arranged in several folders divided into incoming mail folders and outgoing mail folders and left to pile up on the table and placed in a filing cabinet The conclusion of this writing is that the archive management system at the Wayame Village office is not good because it does not comply with existing procedures and the archive storage facilities are also inadequate because they only use one cupboard and folder for storage and some are placed on the employee's desk. The employee who handles the archive should take part in archival training so that they better understand good archival management. Keywords: Archive Arrangement